PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PEMETAAN POTENSI PELUANG USAHA KREATIF MASYARAKAT DESA SIGERONGAN KABUPATEN LOMBOK BARAT - Lilik Handajani; Akram Akram; Ayudia Sokarina (Universitas Mataram, 2022)
The growth of village community groups that are active and have creative ideas will strengthen the acceleration of economic empowerment of rural communities. Businesses initiated by the community individually or in groups are carried out on a small scale, not yet managed properly with the short term aim of taking advantage of existing opportunities to earn income. Although the nature of the business is still seasonal by taking advantage of trends that are currently in demand, this creative effort from the participation of the village community has the potential to be developed in the future. The purpose of this partnership community service activity is to map creative businesses that arise from rural communities who have creative ideas by identifying business opportunities, obstacles and problems as well as prospects for future business development. The mapping was carried out through a survey of village community groups who run creative businesses in the Sigerongan Village, Lingsar District, West Lombok Regency. Mapping the local potential of the village is needed, including business development opportunities from local potentials that may not appear, but have business prospects in the future. The results of this activity can identify opportunities, constraints and prospects for creative business in rural communities that can be used to open up new opportunities and initiate joint venture groups (KUBe) to obtain external funding opportunities through business development. This activity will also assist the stakeholders of Sigerongan Village in formulating a development strategy in planning the economic empowerment of the village community independently. Real mapping of potential opportunities, constraints and prospects for community-based business participation is needed to support the development of an advanced and independent village.